Analisis Responsifitas Pada Pasien BPJS di Puskesmas Padamukti - Hakim, Abdul; Fitria, Ida Jalilah (Jurnal Online Manajemen ELPEI, 2025)
This study aims to analyze the level of responsiveness of services to BPJS patients at Padamukti Community Health Center and identify factors influencing this responsiveness. The background of this study is based on the discrepancy between negative online reviews from the public and field findings that indicate high patient satisfaction with healthcare services. This study used a qualitative approach with data collection methods including interviews, observation, and documentation. Data analysis was conducted thematically based on responsiveness indicators such as speed of service, empathy, staff attitude, and effectiveness of service flow. The results showed that responsiveness of services at Padamukti Community Health Center was assessed as good by patients, supported by training of healthcare workers, the implementation of a queuing system, and more humanistic communication. These findings are expected to serve as evaluation material and a reference for improving service quality at first-level healthcare facilities (FKTP).